ERROR ANALYSIS OF SUNDANESE ENGLISH STUDENT’ PRONUNCIATION ON FRICATIVE SOUND - Wawat Srinawati; Dhea Tria Septiani (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
This research aims to investige the main factors that cause the students` English pronunciation errors on fricative sound and to identify the types of the students` English pronunciation errors on fricative sound pronounced by Sundanese students at STKIP Muhammadiyah Bogor. The writer collects data and does the following: through interviews with Sundanese students by record the pronunciation and analyze the errors based on the concept of Error Analysis of multiple sources. Research findings indicated that factor and types of error. Firstly, the data found that the most apparent causes or factors of pronunciation errors are: first, the interlingual transfer that affected students` mother tongue Second, the intralingual transfer that focused on students’ target languagegeneralization, inaccurate rules and misunderstand the rules. Third, context of learning that covered in social and classroom situation. Secondly, the writer drew the conclusion based on the analysis of test : It is proven that students make four kinds of errors, namely: Types of English fricative consonant errors made by students are omission errors (28), addition errors (41), formation errors (17), and arrangement errors (6) .